Urban informatics in China: Exploring the emergence of the Chinese city 2.0 - Shang, D.; Doulet, J.; Keane, Michael (IGI Global, 2008)
This chapter examines the development of information and communication technologies (ICTs) in urban China, focusing mainly on their impact on social life. The key question raised by this study is how the Internet and mobile technologies are affecting the way people make use of urban space. The chapter begins with some background to China's emergence as a connected nation. It then looks at common use of web-based and mobile phone technologies, particularly bulletin boards, SMS and instant messaging. The chapter then presents findings of recent research that illustrates communitarian relationships that are enabled by mobility and the use of technologies. Finally, these findings are contextualized in the idea of the City 2.0 in China. © 2009, IGI Global.